Second opinion on insanity plea in a murder and attempted suicide case: A case report - Md Rosli, Najwa Hanim; Yahya , Badi’ah; Abu Bakar , Abdul Kadir (ASEAN Journal of Psychiatry, 2011)
Objective: This paper aims to discuss the issue related to the application of temporary insanity plea through a case report of a man who was earlier certified as mentally sound following a murder and suicide attempt. Methods: We report a man who committed murder and attempted suicide 7 years ago, had a psychiatric certification of not having mental illness and recently requested for a second psychiatric assessment. The factors taken into consideration in arriving at the final diagnosis are discussed.